UPAYA PENINGKATAN HASIL BELAJAR PESERTA DIDIK KELAS 7C UPTD SPF SMPN 1 BONDOWOSO SEMESTER GENAP TAHUN PELAJARAN 2019/2020 DI TENGAH PANDEMI COVID-19 MENGGUNAKAN GOOGLE SITES PADA MATERI KELILINGDAN LUAS BANGUN DATAR: UPTD SPF SMPN 1 BONDOWOSO - SUHARTO (Dewan Pendidikan Bondowoso, 2022)
The presence of the Covid-19 pandemic has caused serious problems in the world of education. This phenomenon forces the world of education to conduct distance learning. One of the efforts to fulfill these conditions can be done by utilizing Google Sites online-based services. This service allows a teacher to continuously monitor and improve skill of students This research is based on the following problems: (a) How is the implementation of Google Sites in improving student learning outcomes? (b) What is the form of improving student learning outcomes after using Google Sites? While the objectives of this research are: (a) Knowing the application of Google Sites in improving student learning outcomes, (b) Knowing the form of improving student learning outcomes after using Google Sites. This study uses the type of action research. The Action as much as 2 cycles. Each cycle consists of four stages, namely: design, observation, reflection, and revision. The target of this research is students of class 7C UPTD SPF SMPN 1 Bondowoso for the 2019/2020 academic year. The data obtained in the form of numbers assigned to students. From the results of the study, it was found that the learning outcomes of students in class 7C UPTD SPF SMPN 1 Bondowoso in 2019/2020 using Google Sites on the area and circumference of flat shapes increased.